Analysis of The Competitiveness of Indonesian Rubber Exports in The Market International - Ulfah, Maulida; Samsir, Andi; Alam, Syamsu (Economics and Business Journal (ECBIS), 2023)
The object of this study is to know the competitiveness of Indonesian rubber and articles thereof (HS 40) export in international market, also the rivals (China and Thailand) by using Revealed Comparative Advantage (RCA) to analyze the comparative advantage and Export Product Dynamic (EPD) to analyze the competitive advantage. The result shows that Indonesia has a comparative advantage and specializes in rubber and articles thereof (HS 40) export above the average of countries’ based on RCA value, but this commodity is not competitive in capturing the international market based on EPD value. This study also finds the weakness of the RCA method that has been unable to identify the relative productivity (comparative advantage) of country. We underlined that RCA valuein this study is not absolutely shows the strength/weakness of the countries.